Service innovation in small neighborhood family firms: An advanced approach to enhance employee's performance through social and psychological rewards - Sadiq, Muhammad Waqas; Hameed, Javaria; Huo, Chunhui; Abdullah, Muhammad Ibrahim (Frontiers in Public Health, 2022)
This research study focuses on the employee's job performance of private small firms during the post COVID-19 situation. After the COVID these small family firms try to regain their business, but their efforts are not that much successful. This situation creates a financial crisis in these firms, and they are unable to provide sufficient monetary rewards to their employees. This situation creates unrest among the employees of these small firms. To manage this issue, social rewards and psychological rewards played their role. The study uses a causal research design with a correlational study design in a non-contrived environment. Minimal researcher interference has been assured. AMOS 24 has dealt with the mediation in study design with bootstrap methodology. The study was conducted on 250 employees of different private small family firms across Punjab province using a proportionate stratified sampling technique. A study's finding suggests that top management enhances employee performance in their organizations by introducing the organization's psychological rewards. In contrast, introducing social rewards does not significantly impact employee performance while considering satisfaction and motivation as a mediating variable.